IN SILICO ANALYSIS OF BIOACTIVITY POTENTIAL AND PHARMACOKINETIC CHARACTERISTICS OF GRASS JELLY (Cyclea barbata) SECONDARY METABOLITES USING PASS ONLINE AND SWISSADME: ANALISIS IN SILICO POTENSI BIOAKTIVITAS DAN KARAKTERISTIK FARMAKOKINETIK METABOLIT SEKUNDER CINCAU HIJAU (Cyclea barbata) MENGGUNAKAN PASS ONLINE DAN SWISSADME - Dimas Tama Suryadinata; Oktaviola Dea; Wildan Yudistira; Rofi Sufyan Zaki; Ana Maria Susana; Abdurrohman Rosyid; Ebenezer; Dodi Iskandar (ROCE : Jurnal Pertanian Terapan, 2026)
Green grass jelly (Cyclea barbata Miers) is a medicinal plant that contains various secondary metabolites with potential as sources of phytopharmaceutical candidates. This study aimed to analyze the bioactivity potential, drug-likeness characteristics, pharmacokinetic profile, medicinal chemistry properties, and toxicity of secondary metabolites present in Cyclea barbata using an in silico approach. The identified compounds were analyzed using PASS Online for biological activity prediction, SwissADME for drug-likeness and pharmacokinetic evaluation, and pkCSM for ADME/T (Absorption, Distribution, Metabolism, Excretion, and Toxicity) prediction. The results showed that tyramine and dopamine exhibited the highest biological activity as serotonin-release stimulants and MAP kinase pathway activators. Coclaurine, norcoclaurine, and N-methylcoclaurine demonstrated favorable drug-likeness profiles by satisfying most of the Lipinski, Veber, and Egan criteria. Pharmacokinetic analysis indicated that most simple compounds possessed high gastrointestinal absorption, whereas complex alkaloids such as tetrandrine and fangchinoline exhibited broader tissue distribution potential and greater blood–brain barrier permeability. Medicinal chemistry evaluation revealed that all compounds were free from PAINS alerts, while toxicity prediction indicated relatively favorable safety profiles for most compounds. The findings suggest that Cyclea barbata has considerable potential as a source of bioactive compounds for the development of modern phytopharmaceuticals, particularly as neuroprotective and anti-inflammatory agents. However, further validation through in vitro and in vivo studies is required to confirm the efficacy and safety of the predicted compounds.